Emerging cases of pertussis among early infants born to unvaccinated mothers, an infectious disease long absent in Northwestern Greece - Alexandros Makis; Vasileios Grammeniatis; Charis Galati; Panagiota Kostara; Evangelia Petridou; Constantina Gartzonika; Athanasios Pappas; Nikolaos Chaliasos (Mediterranean Journal of Hematology and Infectious Diseases)
N/A